A Note On Delaval Somatic Cell Count (Dscc) As A Screening Tool For Suboptimal Udder Health In Buffaloes - Sumathi, D.; Venkatesan, M.; Selvaraj, P.; Nambi , A.P. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Subclinical mastitis cause reduction in milk quality and its market value as well as it is responsible for up to 70% of the losses in mastitis (Kirk et al 1988). Buffaloes often suffer from udder health issues and subclinical mastitis often goes undetected. Detection of suboptimal udder health issues is the major challenge for the practicing veterinarians. Milk constituent monitoring has the higher diagnostic potential and can be used at the field level. Somatic cells are part of the natural defense mechanism and include lymphocytes, macrophages, polymorphonuclear cells and some epithelial cells (Pillai et al., 2001).These Somatic cells are mostly cells of the immune system (80% in uninfected quarters, 99% in mastitic quarters) (Sordillo et al., 1997). Somatic cells are therefore a reflection of the inflammatory response to an intramammary infection or another trigger of the immune system.